2021
DOI: 10.1136/jech-2020-215392
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related health inequality exists even in a city where disease incidence is relatively low: a telephone survey in Hong Kong

Abstract: BackgroundWe examined whether COVID-19 could exert inequalities in socioeconomic conditions and health in Hong Kong, where there has been a relatively low COVID-19 incidence.Methods752 adult respondents from a previous random sample participated in a telephone survey from 20 April to 11 May 2020. We examined demographic and socioeconomic factors, worry of COVID-19, general health, economic activity, and personal protective equipment (PPE) and related hygiene practice by deprivation status. The associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
(22 reference statements)
3
20
1
Order By: Relevance
“…Taken together, those who were worried about personal savings, who also tended to be of a lower socioeconomic position in Hong Kong, may have experienced a greater level of psychosocial distress under the pandemic-related economic downturn. This is also in line with the previous COVID-19 research in Hong Kong supporting a partial mediation of inequalities in mental health via people's concerns over livelihood and economic activity (68,69). Furthermore, studies in Hong Kong also revealed that the socially deprived individuals tended to be more concerned about PPE as they had lower reserves and hence utilization (68,70), which may help explain why to worry about personal savings acted as a risk factor of personal hygiene practices but a facilitator of reduced social gatherings in Hong Kong.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, those who were worried about personal savings, who also tended to be of a lower socioeconomic position in Hong Kong, may have experienced a greater level of psychosocial distress under the pandemic-related economic downturn. This is also in line with the previous COVID-19 research in Hong Kong supporting a partial mediation of inequalities in mental health via people's concerns over livelihood and economic activity (68,69). Furthermore, studies in Hong Kong also revealed that the socially deprived individuals tended to be more concerned about PPE as they had lower reserves and hence utilization (68,70), which may help explain why to worry about personal savings acted as a risk factor of personal hygiene practices but a facilitator of reduced social gatherings in Hong Kong.…”
Section: Discussionsupporting
confidence: 91%
“…This is also in line with the previous COVID-19 research in Hong Kong supporting a partial mediation of inequalities in mental health via people's concerns over livelihood and economic activity (68,69). Furthermore, studies in Hong Kong also revealed that the socially deprived individuals tended to be more concerned about PPE as they had lower reserves and hence utilization (68,70), which may help explain why to worry about personal savings acted as a risk factor of personal hygiene practices but a facilitator of reduced social gatherings in Hong Kong. Adopting personal hygiene practices may be costly and so they engaged in these behaviors less frequently; instead, reducing social gatherings can help them save money and PPE.…”
Section: Discussionsupporting
confidence: 91%
“…An online study on Russian-speaking healthcare workers also found that the increase in anxiety concerns about COVID-19 was associated with an increase in psychological distress ( 8 ). Moreover, it has been determined that even in regions with low rates of SARS-CoV-2 infection, COVID-19 worry significantly contributes to a general population's worsened mental health ( 9 11 ). As an illustration, a recent study in Hong Kong showed that compared to individuals who were less worried about COVID-19, those who were more worried about COVID-19 were more likely to have mental health problems ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies have reported that the effect of COVID-19 worry on mental health might vary between social groups with different demographic characteristics and economic statuses. In particular, sex, age, and socioeconomic status have been determined to be key factors mediating the impact of COVID-19 worry on mental health ( 2 , 9 , 12 , 13 ). First, some studies have shown that women are more likely than men to suffer mental health problems due to COVID-19 worry ( 2 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hong Kong could serve as an exemplary setting for an in-depth investigation of the socioeconomic inequalities in COVID-19 severity. Compared with many other regions with widespread community COVID-19 outbreaks, Hong Kong has a relatively low COVID-19 incidence with less than 9000 confirmed cases and 150 deaths by the end of 2020 [14,15]. In addition to the better-controlled COVID-19 outbreak, the public-private dual-track healthcare system in Hong Kong also has a strong equity impact on both COVID-19 treatment and socioeconomic inequalities in chronic disease management.…”
Section: Introductionmentioning
confidence: 99%